The Analysis of Factors Influencing Decisions on The Use of Sharia Banking in Generation Z in Jakarta - Radja Rabbani Mahesazzumar; Mira Rahmi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Islamic banking is currently growing and continues to have positive growth in recent times. Although the development is very rapid, it is still quite difficult for Islamic banking to compete with conventional banking. The study aimed to analyze the effect of the variables of religiosity, reputation, and location on the decision of Generation Z to use Islamic banking, especially in Jakarta. The data collection technique used a purposive sampling technique with 91 Islamic bank customers. The data analysis technique with SmartPLS 3.2 software. The results of the study are as follows (1) The religious variables have an insignificant effect on the decision to use Islamic banks, (2) the reputation variable has a significant effect on the decision to use Islamic banks, and (3) the location variable has a significant effect on the decision to use Islamic banks. The limitations of the study where the researcher only uses three independent variables and relatively small because it is only Generation Z in Jakarta. Hopefully, the research will be helpful for Islamic banking to take action to continue to improve its reputation and increase the distribution of bank locations to reach more people.